Determinants of Monkeypox Awareness and Vaccination Willingness among Healthcare Workers in Pakistan - Rabbiya Ahmad; Sara Ahmad; Araj Hussain; Shaib Muhammad; Ali Qureshi; Ishaqui, Azfar Athar; Narendar Kumar (Journal of Liaquat University of Medical & Health Sciences, 2026)
Objective: This study assessed the healthcare workers' knowledge, attitudes, perceptions (KAP), and willingness to vaccinate against Monkeypox in Pakistan. Methodology: A cross-sectional study was conducted among healthcare workers (HCWs) aged 22 years and older using a self-administered online survey. Participants were enrolled using convenience and simplified snowball sampling, while non-healthcare workers were excluded. Data were analyzed using IBM SPSS software version 26. RESULTS: A total of 420 participants were included, with a predominance of females (57.1%). Most participants were single (61.4%), university graduates (72.1%), and pharmacists (69.3%) working in the private sector (61.4%) and urban areas (80.7%) of the Sindh region (49.3%). Good knowledge of Monkeypox (Mpox) was observed in 65.7% of participants, with high awareness of the association between Mpox and skin lesions (90.0%) and preventive measures (90.0%). However, only 28.6% were aware of its case-fatality ratio. Predictors of good knowledge included previous awareness of Mpox (aOR 2.24; p<0.001) and concern about Mpox (aOR 2.47; p<0.001), while poor knowledge was associated with being from Sindh (aOR 0.48; p=0.003) or KPK (aOR 0.29; p=0.004). Positive attitudes toward vaccination were associated with being male (aOR 1.91; p = 0.035), working in tertiary care hospitals (aOR 1.86; p = 0.036), and concern about Mpox (aOR 1.95; p = 0.020). Most participants (68.6%) favored free vaccination initiatives. CONCLUSION: Promoting Monkeypox vaccination among populations may be improved with more deliberate transmission of common information about Mpox among HCWs.